A comparative study of exteriorization and intraperitoneal closure of uterus in caesarean delivery - K. R., Bharathi; G., Mahendra; S., Vindhyshree; Sherawath, Sonia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Caesarean delivery is the most common intraperitoneal surgical procedure in obstetrics. Many surgical techniques for caesarean delivery have been described, and the debate about the ideal caesarean technique to minimize morbidity is going on still. The aim of this study was to assess the intraoperative and postoperative advantages and disadvantages following exteriorization of uterus at caesarean section with intraperitoneal repair of uterus. Methods: It is a randomized controlled trial conducted at Adichunchanagiri Institute of Medical Sciences, B G Nagar, Mandya. Minimum of 100 cases, 50 each were randomly allocated into case and control groups. All patients who were undergoing emergency and elective caesarean delivery under spinal anaesthesia were randomly allocated into exteriorization and intraperitoneal group. In exteriorization group, uterus is exteriorized after delivery of foetus and placenta for repair, whereas in intraperitoneal group in situ repair was done. A pfannenstiel incision was taken for all the cases. Placenta was removed either by controlled traction after spontaneous separation or manually. Uterus was exteriorized after delivery of placenta and may be repaired by single or double layer. Visceral and parietal peritoneum are not closed. Results: There is significant difference in the operating time in the exteriorization group and in the in-situ group. But no significant difference between 2 groups regarding nausea, vomiting intra operatively, in return of bowel function, number of analgesic doses, incidence of cystitis, endometritis and wound infection. Period of hospitalization were also same in both groups. Conclusion: Exteriorization of uterus at caesarean delivery has the advantages less perioperative haemoglobin reduction, good exposure, good access to incision angle, especially during difficult extraction. Easy identification of uterine anomaly, adnexal mass if present and exposure of posterior aspect of lower segment.